2018
DOI: 10.1177/2325967118807906
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Anatomic Glenoid Reconstruction: Analysis of the Learning Curve

Abstract: Background:Anatomic glenoid reconstruction involves the use of distal tibial allograft for bony augmentation of the glenoid surface. An all-arthroscopic approach was recently described to avoid damage to the subscapularis tendon and preserve the capsule and labrum.Purpose:To explore and compare change in surgical time between 2 proposed methods used for the treatment of anterior shoulder instability—arthroscopic anatomic glenoid reconstruction (AAGR) and arthroscopic Latarjet (AL)—over successive procedures. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…There were two studies that described a technique and presented cadaveric findings 39 40. There were eight studies that present results using one of the previously described techniques 16 17 19–22 26. This means that there are 19 described techniques.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were two studies that described a technique and presented cadaveric findings 39 40. There were eight studies that present results using one of the previously described techniques 16 17 19–22 26. This means that there are 19 described techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies reported outcomes including patient satisfaction, functional scores, range of motion (ROM), radiographic findings and recurrence of instability. There are 12 studies that report outcomes 15–17 19–27. These outcomes are presented in tables 3 and 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Arthroscopic anatomic glenoid reconstruction using distal tibial allograft is a newly described surgical technique with a relatively fast learning curve and high rates of desired graft position compared with the arthroscopic Latarjet procedure. 13 This technique has been originally described by Wong and Urquhart in 2015. 11 The arthroscopic procedure allows us to place the graft at the desired location and flush with the adjacent glenoid fossa.…”
Section: Discussionmentioning
confidence: 99%